Role of the Internal Auditors in Improving the Quality Management System Integrated ISO 9001:2015 and 22716:2007 - Lutfiah Khairunnisa; Maidani (Journal of Research in Business, Economics, and Education, 2020)
This study aims to determine the role of internal auditors at PT. Orson Indonesia is in order to improve the quality of management systems that are integrated with ISO 9001: 2015 and 22716: 2007. With a qualitative method that is descriptive analysis based on direct observation to the field and with documents that support to be traced. The techniques used are interviews, observation, document analysis, literature study and questionnaires. The results showed that PT. Orson Indonesia has successfully implemented this ISO Quality Management System with the existence of internal audit activities assisted by auditors and adequate data or documents.